The Morphophonology of Intraword Codeswitching: Representation and Processing - Stefanich, Sara; Cabrelli, Jennifer; Hilderman, Dustin; Archibald, John (Frontiers in Communication, 2019)
This paper serves as a critical discussion of the phenomenon of intraword code-switching (ICS), or the combining of elements (e.g. a root and an affix) from different languages within a single word. Extensive research over the last four decades (Poplack, 1988; MacSwan, 2014; Myers-Scotton, 2000) has revealed CS to be a rule-governed speech practice. While interword CS is widely attested, intraword code-switching has been argued to be impossible (Bandi-Rao & DenDikken, 2014; MacSwan & Colina, 2014; Poplack, 1980).However, ICS has recently been documented in language pairs ranging from English/Norwegian (Alexiadou, Lohndal, Afarli & Grimstad, 2015) to Nahuatl/Spanish (MacSwan, 1999) to Greek/German (Alexiadou, 2017), and is a robust phenomenon.We review the foundational research on ICS, followed by an examination of the phenomenon from the perspectives of knowledge and skill. First, we examine intraword CS as part of a bilingual’s I-language to determine the morphological and phonological restrictions on the phenomenon. We operationalize these restrictions within a Distributed Morphology (DM) framework (e.g., Halle & Marantz, 1994) in which the traditional lexicon is split into three lists. List 1 contains lexical roots and grammatical features or feature bundles, while Lists 2 and 3 detail instructions for phonological realization (i.e., rules for Vocabulary Insertion) and semantic interpretation, respectively. Here we probe the question of whether words which have morphological mixing also have phonological mixing. Second, building on the DM machinery, we present an account for intraword CS in performance via the modular cognitive performance framework of MOGUL (Truscott & Sharwood Smith, 2014). This modular architecture assumes a) that lexical items are constituted by chains of representations and b) that extra-linguistic cognitive mechanisms (e.g. goals, executive control) play a role in ICS (Green & Abutalebi, 2013). ICS is licensed by a bilingual mode of communication (following Grosjean, 1998) where the act of CS itself serves an illocutionary goal; it is the real-world context which triggers the complex CS system. Thus, viewing intraword CS as an I-language and an E-language phenomenon provides an explanatory model of the dynamic knowing that and knowing how which is manifest in the phenomenon of ICS.